2021
DOI: 10.1155/2021/9749474
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and development of Serratiopeptidase enteric coated tablets and analytical method validation by UV Spectroscopy

Abstract: Serratiopeptidase (SRP) is a proteolytic enzyme that emerged as one of the most potent anti-inflammatory and analgesic drugs. The purpose of the present study was to formulate and evaluate enteric-coated tablets for SRP and investigate their stability using a simple and validated analytical method by ultraviolet (UV) spectroscopy. The colloidal silicon dioxide (2.50%), sodium starch glycolate (3.44%), and crospovidone (2.50%) were used as appropriate excipients for the development of core part of tablets. To p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The sensitivity of the assay method of LCZ was examined with six times repeating the calibration curve, and SD intercepts were measured with the help of the following formula prior to examine the value of LOD and LOQ. where SD = standard deviation of Y intercept of 6 calibration curves and slope = average slope of the 6 calibration curves [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the assay method of LCZ was examined with six times repeating the calibration curve, and SD intercepts were measured with the help of the following formula prior to examine the value of LOD and LOQ. where SD = standard deviation of Y intercept of 6 calibration curves and slope = average slope of the 6 calibration curves [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…where SD � standard deviation of Y intercept of 6 calibration curves and slope � average slope of the 6 calibration curves [19].…”
Section: Limit Of Detection (Lod) and Limit Of Quantification (Loq) D...mentioning
confidence: 99%
“…Enteric coated tablets are the most commonly available form of serratiopeptidase. Panthi et al [ 64 ] formulated enteric coated tablets for serratiopeptidase, which exhibited persistent, stable, and significantly high drug release in the intestine. In general, glyceryl monooleate-based systems give protection to metallo-enzymes in the gastric environment.…”
Section: Clinical Significancementioning
confidence: 99%
“…In general, glyceryl monooleate-based systems give protection to metallo-enzymes in the gastric environment. In addition, they enhanced the sustained release of the enzyme after oral administration [ 64 ]. Shah and Paradkar [ 65 ] suggested that a microenvironment-controlled, in situ, cubic phase transforming glyceryl monooleate system may give protection to serratiopeptidase as well as meticulous release.…”
Section: Clinical Significancementioning
confidence: 99%
“…where SD is the standard deviation of Y-intercept of 6 calibration curves and Slope is the average slope of the 6 calibration curves [21,22].…”
Section: Limit Of Detection (Lod) and Limit Of Quantitation (Loq)mentioning
confidence: 99%